2014
DOI: 10.1590/s0102-71822014000500018
|View full text |Cite
|
Sign up to set email alerts
|

Percepção de adolescentes não-pais sobre projetos de vida e sobre a paternidade adolescente

Abstract: RESUMONa adolescência, há o estabelecimento de projetos de vida, que podem ser modificados frente à situação de paternidade. Assim, o objetivo deste estudo foi investigar a percepção de adolescentes não-pais sobre os projetos de vida e sobre a paternidade adolescente. Em particular, buscou-se examinar suas percepções sobre o impacto de uma gravidez na adolescência nos projetos de vida, em relação à família, à escola e ao trabalho. Foram entrevistados sete adolescentes não-pais, com idades entre 13 e 16 anos, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…In the literature review by Dellazzana-Zanon and Freitas (2015), 10 out of the 14 included articles in Portuguese did not provide an explicit definition of LP. This finding reinforces the fact that the term LP is often used without a clear definition (Venturini & Piccinini, 2014). Furthermore, Neiva-Silva (2003) highlighted that the term LP has been frequently employed interchangeably with other concepts related to people’s psychological future, such as the future time perspective, future expectations, and aspirations.…”
supporting
confidence: 83%
“…In the literature review by Dellazzana-Zanon and Freitas (2015), 10 out of the 14 included articles in Portuguese did not provide an explicit definition of LP. This finding reinforces the fact that the term LP is often used without a clear definition (Venturini & Piccinini, 2014). Furthermore, Neiva-Silva (2003) highlighted that the term LP has been frequently employed interchangeably with other concepts related to people’s psychological future, such as the future time perspective, future expectations, and aspirations.…”
supporting
confidence: 83%
“…(18) Other studies show that adolescent paternity contributed to the consolidation of masculinity in adolescent men by assuming the role of guardian's economic providers of the new family; Therefore, it was a positive experience that allowed them to stop being teenagers and become men; (19)(20)(21) however, in another research, for some adolescent men the experience of adolescent paternity was negative, if That was associated with personal, economic and family problems. (22) The present research found that most of the adolescent parents had not completed their high school studies, were of low socioeconomic strata, received financial aid from the state and some had support from their families. About the foregoing, several investigations reiterate the importance of understanding the economic, political, social and cultural context of adolescents, as the experience of adolescent fatherhood is directly influenced by their Context and the family support with which the adolescent men count.…”
Section: Discussionmentioning
confidence: 55%
“…Esse balanço estatístico apresenta quadros de mudanças no cenário nacional, frente ao anseio de formar família e/ou de romper com essas relações. De toda forma, considera-se que o casamento ainda se constitui como meta de muitas pessoas, especialmente entre a população jovem que expressa o desejo de se casar (Riter et al, 2019;Venturini & Piccinini, 2014), embora a faixa etária de nupcialidade tenha aumentado em comparação às décadas passadas. A média etária das uniões civis para as mulheres heterossexuais brasileiras corresponde a 27 e 29 anos e para os homens heterossexuais a 30 e 32 anos.…”
Section: Mots-clés : Satisfaction Conjugale Qualité Conjugale Ajustem...unclassified